2020
DOI: 10.1152/ajpcell.00035.2020
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing and fibrosis: a contrasting role for periostin in skin and the oral mucosa

Abstract: Both skin and oral mucosa are characterized by the presence of keratinized epithelium in direct apposition to an underlying collagen-dense connective tissue. Despite significant overlap in structure and physiological function, skin and the oral mucosa exhibit significantly different healing profiles in response to injury. The oral mucosa has a propensity for rapid restoration of barrier function with minimal underlying fibrosis, but in contrast, skin is associated with slower healing and scar formation. Modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 115 publications
2
62
0
Order By: Relevance
“…The skin and gingiva, typical body covering tissues, are considered structurally and functionally homogenous tissues showing similar healing patterns in response to injury. Both are characterized by the presence of keratinized epithelium with underlying connective tissue, which acts as a barrier to microorganisms and other contaminants [ 9 ].…”
Section: Normal Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin and gingiva, typical body covering tissues, are considered structurally and functionally homogenous tissues showing similar healing patterns in response to injury. Both are characterized by the presence of keratinized epithelium with underlying connective tissue, which acts as a barrier to microorganisms and other contaminants [ 9 ].…”
Section: Normal Wound Healingmentioning
confidence: 99%
“…Recent research has revealed the molecular differences between oral and skin wound healing. Most studies have suggested that an oral wound is in the “primed” state for wound healing compared to a skin wound ( Table 1 ) [ 9 , 15 , 16 , 17 ].…”
Section: Distinct Characteristics Of the Oral Woundmentioning
confidence: 99%
“…Interestingly, there are few physiological paradigms where wounds heal scarlessly or with minimal scarring, for instance the wounds in the early gestation fetus and in the oral mucosa of mammals heal without scar [6] the transition from scarless to scarred healing occurs in humans during late weeks of gestation [7]. A recent study showed that dermal fibroblasts with a scarring phenotype when transplanted into oral mucosa ended up generating more scar-like connective tissue compared with oral mucosal fibroblasts transplanted into the dermis [8]. The oral mucosal fibroblasts were shown to possess a higher baseline production capacity of several ECM-associated proteins than the skin fibroblasts, except type III collagen, which could be possibly attributed to a more favorable wound healing in oral mucosa [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed in various normal tissues, often associated with fibroblasts, and involved in remodeling of the extracellular matrix environment. [ 1 , 2 ] In some disease states, such as myocardial infarction, cancer, liver fibrosis, and pathologic scarring of the skin, periostin is reportedly a vital regulator of the progression of the disease and significantly over-expressed. [ 3 ] This article summarizes recent advancements in studies on the role of periostin in skin wound healing and pathologic scar formation.…”
mentioning
confidence: 99%
“…Previous studies have reported the positive function of periostin in promoting proliferation and differentiation of fibroblasts, keratinocytes, and mesenchymal cells in the wound, resulting in appropriate re-epithelialization and myofibroblast differentiation in the granulation tissue, thus gradually closing the wound. [ 1 , 6 , 9 ] Elliott et al [ 6 ] reported that full-thickness skin wounds were significantly larger in periostin-knockout mice than those in wild type mice at 5 and 7 days after wounding, and α-smooth muscle actin (α-SMA) was significantly down-regulated in wounds of periostin-deficient-mice. Moreover, Ontsuka et al [ 7 ] reported that the intervals for wound closure were significantly extended in periostin-knockout mice than those in wild type mice, suggesting that periostin could affect wound re-epithelialization.…”
mentioning
confidence: 99%